The book of radical answers : real questions from real kids just like you - Taylor, Sonya Renee (Dial Books for Young Readers, 2023)
"A nonfiction guide to growing up rooted in radical self-love and body empowerment that answers real questions from kids about health, sex, gender, race, justice, and more"--